Improved gear metrology based on the calibration and compensation of rotary table error motions. Issue 1 (2019) - Wang, Qichang; Peng, Yue; Wiemann, Ann-Kathrin; Balzer, Felix; Stein, Martin; Steffens, Norbert; Goch, Gert
Abstract: Geometric measurements of cylindrical gears are mainly conducted by either applying the generation principle or by coordinate measurements of points on a flank surface. In both cases, a rotary table (RT) is highly involved in the inspection process. The RT error motions and the misalignments of the gear axis with respect to the table's effective rotary axis affects the measurement results, whose impacts increase with the gear dimensions. This paper presents the influence of such errors on gear measurements using both the classical line oriented and the areal inspection methods. A compensation method to remove these influences in gear evaluations is proposed using a RT, which was calibrated with a ball plate artifact. The methods are validated by measuring and evaluating a large gear artifact applying multiple strategies with and without compensation.